2006
DOI: 10.1021/ma060407+
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Stress Relaxation in Highly Stretched Samples of Natural Rubber and Its Synthetic Analogue

Abstract: Vulcanizates of natural rubber (NR) and its synthetic analogue (IR) were quickly stretched to 6 times the original length. The post stretch relaxation of tensile stress and the development of strain-induced crystallization (SIC) were studied by simultaneous measurements of the stress and the diffraction intensities using the synchrotron X-ray source. In the range of 8 s, NR crystallized much faster than IR. Accordingly, the origin of the superior toughness of NR was thought to come from the ability of rapid SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
94
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 22 publications
10
94
2
Order By: Relevance
“…The crystallinity was followed by WAXD and the results showed a small shifting towards higher values for λ A . These measurements confirmed that the results obtained by Miyamoto et al 51 for IR are also valid for NR. However, the faster SIC kinetics for NR compared to IR reduces this strain rate effect.…”
Section: Strain Ratesupporting
confidence: 91%
See 1 more Smart Citation
“…The crystallinity was followed by WAXD and the results showed a small shifting towards higher values for λ A . These measurements confirmed that the results obtained by Miyamoto et al 51 for IR are also valid for NR. However, the faster SIC kinetics for NR compared to IR reduces this strain rate effect.…”
Section: Strain Ratesupporting
confidence: 91%
“…The work of Choi and Roland 50 on NR crosslinked with peroxide confirms this kind of evolution for stress relaxation. Similar results have been established by WAXD on NR and IR by Tosaka et al, 51 who showed that SIC kinetics and consecutively stress relaxation are much slower in the case of IR. The short-term crystallization for a static stretch is much more difficult to analyze than long-term crystallization because λ max is never reached instantaneously; moreover, conventional x-ray diffraction requires slow data acquisition (typically few minutes) that is not compatible with the study of short-time effects.…”
Section: Strain-induced Crystallization and Mechanical Behavior supporting
confidence: 89%
“…Such a big difference in i would have been detectable. 50,51 presented that the initial rate of SIC is faster for the samples with the higher . Then the predicted dependence of i on would appear more strongly, if the kinetics has really affected.…”
Section: Incipient Strain Of Crystallizationmentioning
confidence: 99%
“…These results are consistent with the classic experimental studies. 9,11 Tosaka et al 50,51 studied SIC and corresponding stress relaxation during the shorter time ranging ca. 8 s to 30 min for NR and IR samples with various .…”
Section: Crystallization Under Constant Strainmentioning
confidence: 99%
See 1 more Smart Citation